Warm-Glow Giving in Networks with Multiple Public Goods - Lionel Richefort (Fondazione Eni Enrico Mattei (FEEM), 2017)
This paper explores a voluntary contribution game in the presence of warm-glow effects. There are many public goods and each public good benefits a different group of players. The structure of the game induces a bipartite network structure, where players are listed on one side and the public good groups they form are listed on the other side. The main result of the paper shows the existence and uniqueness of a Nash equilibrium. The unique Nash equilibrium is also shown to be locally asymptotically stable. Then the paper provides some comparative statics analysis regarding pure redistribution, taxation and subsidies. It appears that small redistributions of wealth may sometimes be neutral, but generally, the effects of redistributive policies depend on how public good groups are related in the contribution network structure.
Keywords: C72; D64; H40; 330; Multiple Public Goods; Warm-glow Effects; Bipartite Contribution Structure; Nash Equilibrium; Comparative Statics